2005
DOI: 10.1177/153331750502000210
|View full text |Cite
|
Sign up to set email alerts
|

Activity situations on an Alzheimer's disease special care unit and resident environmental interaction, time use, and affect

Abstract: Routine activity situations on an Alzheimer's disease (AD) special care unit were examined with respect to residents' social and physical environmental interactions, time use, and apparent affect. Using a computer-assisted observational tool, observers recorded prevailing activity situations and corresponding behaviors and affects of seven residents every 10 minutes, from 8:00 AM to 8:00 PM, across four days. Although meals/snacks and some activity groups were positively associated with use of physical objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 16 publications
3
82
0
Order By: Relevance
“…Living conditions are important and must be considered [17] . More generally, Wood et al [49] studied the concepts of activity situation and environmental press. They concluded that routine activity situations in an Alzheimer's disease special care unit may be pivotal environmental determinants of the QoL experienced by residents, as well as the therapeutic effectiveness of other social and physical environmental interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Living conditions are important and must be considered [17] . More generally, Wood et al [49] studied the concepts of activity situation and environmental press. They concluded that routine activity situations in an Alzheimer's disease special care unit may be pivotal environmental determinants of the QoL experienced by residents, as well as the therapeutic effectiveness of other social and physical environmental interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One could postulate that the effect of education on cognitive decline is protective at the early stages of disease with more rapid decline in the later stages as the cognitive reserve can no longer overcome the cognitive deficits [54] . In the final stages of disease decline may be rapid, but these patients are excluded from the inception cohort due to inclusion criteria MMSE [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Comparison With Other Longitudinal Studiesmentioning
confidence: 99%
“…The value of non-pharmacological treatments [22][23][24] and social interventions [25][26][27][28] are described along with an increased general understanding amongst healthcare professions as to the multidisciplinary needs of patients and their caregivers. It has been shown that early disease stages are associated with higher patient quality of life [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The first consideration to make in light of this evidence may be that (a) the data need to be viewed with caution as they concern small groups of patients (i.e., eight with previous technologies and four in Study II), and (b) the different outcomes could be more directly related to the characteristics of the patients and/or of the travel routes than to the technology resources per se (Lancioni et al, 2007). An additional consideration may be that even the data of the less successful patients of Study II suggest a practically relevant performance change that could have implications for the patients (i.e., in terms of enhanced social image and travel opportunities) and their environment (i.e., in terms of objectives considered viable for their daily programs) (Brown et al, 2009;Gibson, MacLean, Borrie, & Geiger, 2004;Lancioni et al, 2012Lancioni et al, , 2013Marquardt & Schmieg, 2009;Sunderland, Catalano, & Kendall, 2009;Tsuchiya & Adolphs, 2007;Wood, Harris, Snider, & Patchel, 2005).…”
Section: Discussionmentioning
confidence: 99%